Shaming the silences: Indigenous Graduate Attributes and the privileging of Aboriginal and Torres Strait Islander voices. Issue 1 (1st January 2022) - Bodkin-Andrews, Gawaian; Page, Susan; Trudgett, Michelle
ABSTRACT: An increasing number of Australian universities are committing to Indigenous Graduate Attributes across a wide range of academic disciplines. This paper critiques not only the slow up-take of Indigenous Graduate Attributes in the last 10 years, but also how such attributes may realistically contribute to university students graduating with increased 'awareness', 'knowledges' and 'abilities' to work with Aboriginal and Torres Strait Islander peoples and communities. It is reasoned that any commitment to Indigenous Graduate Attributes must be carefully and critically monitored for the silencing effects of colonial narratives that also are prevalent throughout Australian Indigenous Studies (which is arguably the foundation of realising Indigenous Graduate Attributes). Drawing from a diversity of Indigenous standpoint theories, critical studies and research methodologies, the paper offers a critical evaluative framework through which both Indigenous Graduate Attributes and the content within the teaching and learning of Australian Indigenous Studies may be evaluated. This includes an acute awareness of imposed colonial narratives, a critical awareness of one's own positioning, engagement with Indigenous voices, knowledge of Indigenous Research Methodologies, and more meaningful levels of Indigenous engagement through Indigenous ethics and protocols.